Latitudinal Response of Storm Activity to Abrupt Climate Change During the Last 6, 500 Years. Issue 19 (26th September 2020) - Yang, Yang; Maselli, Vittorio; Normandeau, Alexandre; Piper, David J. W.; Li, Michael Z.; Campbell, D. Calvin; Gregory, Taylor; Gao, Shu
Abstract: This study examines the influence of the strength of Atlantic Meridional Overturning Circulation (AMOC) on storminess at different latitudes in the North Atlantic, based on a new 6.5‐Kyr record of large storms from the Scotian Shelf (Eastern Canada) that provides the first >3.5‐ka record from middle latitudes. Comparison with a compilation of other paleostorm records shows that peaks in storminess are at times synchronous (4.5–2.5 and since 0.5 ka) between low and middle latitudes but in the intervening period (2.5–0.5 ka) were latitudinally asynchronous. Synchronous (asynchronous) behavior correlates with sustained increase (decrease) of AMOC. Regime shifts in storm activity between low and middle latitudes were more frequent since 2.5 ka, related to increased frequency of abrupt climate changes. These findings indicate a latitudinal response of storm activity due to abrupt climate change, which is critical to correctly assess future storm risks along the North Atlantic coastline. Plain Language Summary: The Atlantic Meridional Overturning Circulation (AMOC) is one of the well‐established tipping elements of the Earth's climate system, redistributing heat and thus influencing storm activity. Yet critical questions remain unanswered regarding the latitudinal response of storm activity to AMOC‐related abrupt climate change. Here, we present a storminess record north of 34°N that goes back to >3.5 ka, namely, a 6.5‐Kyr record from the Scotian Shelf (Eastern Canada). We describe for the first time the impact of abrupt climate change on storminess at different latitudes in the North Atlantic in response to changes in AMOC strength. This is based on a comparison of our study with a compilation of other paleostorm records. Synchronous (asynchronous) behavior correlates with sustained increase (decrease) of AMOC. Such information is fundamental to correctly assess future storm risks along the North Atlantic coastline, especially in densely populated coastal areas. Key Points: We provide the first reconstruction of >3.5‐ka record of large storms north of 34° N in the North Atlantic Peaks in storminess in the past 4.5 Kyr are for some periods synchronous at low and middle latitudes; during other periods this is not so Sustained increase of AMOC results in latitudinal synchroneity of storm activity; asynchronous activity results from decreasing AMOC